Design of a biocatalytic cascade for the enzymatic sulfation of unsulfated chondroitin with in situ generation of PAPS - Monterrey, Dianelis T.; Benito-Arenas, Raúl; Revuelta, Julia; García-Junceda, Eduardo (Frontiers in Bioengineering and Biotechnology, 2023)
Sulfation of molecules in living organisms is a process that plays a key role in their functionality. In mammals, the sulfation of polysaccharides (glycosaminoglycans) that form the proteoglycans present in the extracellular matrix is particularly important. These polysaccharides, through their degree and sulfation pattern, are involved in a variety of biological events as signal modulators in communication processes between the cell and its environment. Because of this great biological importance, there is a growing interest in the development of efficient and sustainable sulfation processes, such as those based on the use of sulfotransferase enzymes. These enzymes have the disadvantage of being 3'-phosphoadenosine 5'-phosphosulfate (PAPS) dependent, which is expensive and difficult to obtain. In the present study, a modular multienzyme system was developed to allow the in situ synthesis of PAPS and its coupling to a chondroitin sulfation system. For this purpose, the bifunctional enzyme PAPS synthase 1 (PAPSS1) from Homo sapiens, which contains the ATP sulfurylase and APS kinase activities in a single protein, and the enzyme chondroitin 4-O-sulfotransferase (C4ST-1) from Rattus norvegicus were overexpressed in E. coli. The product formed after coupling of the PAPS generation system and the chondroitin sulfation module was analyzed by NMR.